1989
DOI: 10.1002/hlca.19890720419
|View full text |Cite
|
Sign up to set email alerts
|

New Spirostaphylotrichins from Staphylotrichum coccosporum

Abstract: The isolation and structure elucidation of the new spirostaphylotrichins B (2), C and D (3/4), F (5), Q (6), and R (7) are described. Compounds 2 and 3 are artefacts formed during the isolation of the metabolites from the cultures. The absolute configuration of spirostaphylotrichin A (1) has been determined by CD spectroscopy.Introduction. -Spirostaphylotrichin A (1) is a secondary metabolite which has been isolated by Peter and Auden [ 11 from cultures of the fungus Staphylotrichurn coccosporum. Its structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 2 publications
2
35
0
Order By: Relevance
“…The signal for H8 in the spectrum of the diacetate 10 is a doublet (J = 4.0 Hz) and significant nOe's are observed to the signals of H4, H6a, and H9, thereby supporting the relative stereochemistry assigned to C8, as well as that of C4. Irradiation of the C12 methyl singlet at 6 1.44 in the spectrum of the diacetate 10 results in only a small nOe to the acetate singlets at 6 2.094 and 6 2.085 (1.2% combined) but nevertheless is consistent with the structure assigned to cycloarthropsadiol C (9). Cycloarthropsotze (12)…”
Section: Arthropsadiol B (3)supporting
confidence: 52%
See 1 more Smart Citation
“…The signal for H8 in the spectrum of the diacetate 10 is a doublet (J = 4.0 Hz) and significant nOe's are observed to the signals of H4, H6a, and H9, thereby supporting the relative stereochemistry assigned to C8, as well as that of C4. Irradiation of the C12 methyl singlet at 6 1.44 in the spectrum of the diacetate 10 results in only a small nOe to the acetate singlets at 6 2.094 and 6 2.085 (1.2% combined) but nevertheless is consistent with the structure assigned to cycloarthropsadiol C (9). Cycloarthropsotze (12)…”
Section: Arthropsadiol B (3)supporting
confidence: 52%
“…The I3c nlnr spectrum of arthropsolides B (25) Arthropsolide B (25) and C (26) are very similar in terms of structure and instability to the inseparable mixtures of spirostaphylotrichin G (27) and H (28) from Staphylotrichum coccosporum (lo), and triticone A (23) and B (24) from Staplzyloticlzum coccosporum (9) and Drechsleln tritici-repentis (12). Drechslera ti-itici-repentis is a major pathogen of wheat and it has been suggested that the retro-aldol intermediate 29 by which triticone A and B readily interconvert may be responsible for the lesions produced on wheat plants by this fungus (12).…”
Section: And C (26)mentioning
confidence: 99%
“…In the 2D-INADEQUATE spectra of 6 the signal of C4 is correlated not only to the signal of C3 but also to C5 and C9. This suggests that a significant number of molecules of arthropsadiol A (1) have multiple incorporation of sodium [1,[2][3][4][5][6][7][8][9][10][11][12][13] Cz]acetate at C3-C4, C5-C6, and C9-C10. Assuming that Jcc between C4 and C9 is approximately 35-40 Hz, then incorporation of sodium [I ,2-13~,]acetate at C3-C4, C5-C6, and C9-C10 would result in a ddd of satellite peaks due to coupling of C4 to C3, C5, and C9.…”
Section: Incorporation Of Sodium [12-'-'~~lacetatementioning
confidence: 99%
“…3) and its analogues could not be found in the culture broth of FKI-4751. The spirostaphylotricins have been isolated from S. coccosporum (Sandmeier and Tamm 1989). Details on the novel averufin analogues will be reported elsewhere.…”
mentioning
confidence: 99%
“…Conidia ( Udagawa (1997) b Data from Sandmeier and Tamm (1989) Elaeagnus rotundata, Chichi-jima, the Bonin Islands, Tokyo, Japan, 15 June 2007, isolated by K. Nonaka. The holotype and ex-type strain were deposited in the National Museum of Nature and Science (TNS), Tsukuba and Japan Collection of Microorganisms (JCM), Wako, respectively.…”
mentioning
confidence: 99%